Small vessel disease in patients with subarachnoid hemorrhage: Prevalence and associations with vasospasm occurrence, severity and clinical outcomes. Issue 6 (December 2019) - Villain, Adrien; Boulouis, Grégoire; Ben Hassen, Wagih; Rodriguez-Regent, Christine; Trystram, Denis; Edjlali, Myriam; Nataf, François; Sauvageon, Xavier; Sharshar, Tarek; Meder, Jean F; Oppenheim, Catherine; Naggara, Olivier
Purpose: Investigating the associations between cerebral small vessel disease (cSVD) burden and cerebral vasospasm (CVS), delayed cerebral ischemia (DCI) and clinical outcomes in patients with aneurysmal subarachnoid hemorrhage (aSAH). Methods: Consecutive aSAH patients with initial (<7 days after onset) and 3-month follow-up brain magnetic resonance imaging (MRI) and clinical evaluation at 6 months were included. The cSVD burden score was built using MRI criteria. CVS was defined according to transcranial Doppler examination and computed tomography (CT) or digital subtraction angiography. DCI was defined by the appearance of hyperintense fluid-attenuated inversion recovery lesions, with territorial or cortico-subcortical distribution, between initial MRI and 3-month MRI. The modified Rankin scale of ≤2 at 6 months was considered a favorable outcome. Using univariate and multivariable analyses, we investigated the associations between cSVD and CVS, DCI and clinical outcome. Results: A total of 113 patients were included in the study sample (median age 49.1 years (IQR 42.1–60.8), 70/113 females). The burden of cSVD was mild with a median of 0 (IQR 0–1). When comparing patients with no/mild versus those with moderate/severe cSVD burden, we did not find a univariable difference regarding vasospasm occurrence (60% versus 46.1%, p  = 0.54), DCI (20.2% versus 23%, p  = 0.66) or favorable outcome at 3 months (94% versus 83.3%, p  = 0.20). There was a univariable trend towards more frequent favorable outcome in patients with no/milde white matter hyperintensities versus those with moderate/severe white matter hyperintensities (92% versus 85%, p = 0.09). In multivariable models, cSVD markers were not associated with CVS occurrence and severity, DCI or clinical outcome. Conclusions: In patients with mild aSAH, the burden of cSVD as assessed by MRI is minimal and is not associated with CVS, DCI or clinical outcome.